Angola : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper on Angola reports that oil production in Angola accounts for about half of GDP and about 75 percent of government revenue. The projections for the government's fiscal position in the medium term will be crucially dependent on both the value of oil production and the proportion that will accrue to the government. However, in addition to the usual uncertainties associated with projections of the total value of oil output, the government's share has been subject to volatility.